Fragrance preference of essential oil blends for reducing stress and sleep problems in adult women - Sathirachawan, Kanchanapa; Chansiri, Kosum; Sirikate , Deeprom; Sittiprapaporn, Phakkharawat; Rungsiwiwut, Ruttachuk; Saiyudthong, Somrudee (Universa Medicina, 2025)
Background Aromatherapy with a blend of essential oils is an alternative treatment for stress and sleep disturbances, providing stress relief and sleep enhancement, while increasing the efficacy and scent appeal. This study aimed to formulate an essential oil blend with the potential to reduce stress and enhance sleep quality, and to identify the most preferred blend based on participant satisfaction. Methods A cross-sectional study was conducted involving 63 female volunteers aged 25 - 50 years. Three formulations (A, B, and C) of essential oil blends were developed, each with a distinct scent profile—floral, unisex, and aromatic. A preference test was conducted using a sensory evaluation method, assessing participants’ satisfaction of the blends through inhalation. Preferences were quantified using a structured scoring system. Formula B was the most popular and was further refined into two recipes, B1 and B2. B2 emerged as the preferred option, and its primary component was identified using gas chromatography-mass spectrometry (GC–MS). Results Formulation B, rich in bergamot oil, received significantly higher hedonic ratings than Formulation A (p<0.05) and was the most preferred in interviews. Participants recommended a milder, more balanced scent for relaxation and sleep. While B1 and B2 showed no significant differences, B2 was chosen for its higher bergamot content, fresher unisex profile, and reduced floral notes. GC–MS analysis identified limonene, menthol, and linalool as its main components. Conclusion This study demonstrated that an essential oil blend predominantly composed of bergamot oil was most favored by the volunteers, indicating its potential benefits for promoting relaxation.